Evaluasi Kualitas Susu Sapi Perah Berdasarkan Manajeman Pemeliharaan Kandang - Sonya Putri Maharani; Okinara Risada (PT. Faaslib Serambi Media, 2025)
This study evaluated the quality of dairy cow milk through a literature review of husbandry management. Milk quality assessment includes physical, chemical, and microbiological aspects. Low milk quality is often influenced by poor housing management, feed contamination (e.g. Salmonella sp.), and unhygienic milking practices. This research method is a systematic literature review using databases such as Google Scholar, Scopus, and PubMed with keywords